ANALYSIS OF PHYSICAL THERAPIST’™ WORKING POSTURES PERFORMING MYOFASCIAL TECHNIQUES (Cuestiones de Fisioterapia, 2007)
Introduction: manual therapy practice can lead to work-related musculoskeletal disorders in physical therapists due to awkward postures, musculoskeletal workload and repetitive movements while working. The aim of the present study was to determinate physical workload and working posture analysis performing myofascial techniques. Materials and methods: the working postures of a physical therapist were observed during several work cycles and recorded. We collected data from 53 representative postures. The postural assessment was made by Rapid Upper Limb Assessment method. Results: forty-seven postures were classified as action level 2. This suggests that working postures could be harmful to the musculoskeletal system and further investigation is needed. 98 % of all postures used ranges of motion for shoulder flexion from 0° to 45°. Forty-five postures used ranges of motion for elbow flexion from 60° to 100°. We only found five postures used extreme ranges of motion for wrist flexion or extension and pronation/supination movements were extreme almost 40 %of all tasks. Discussion: high percentage of action level 2 tasks that we have found, is due to prolonged static postures since most of them do not use extreme ranges of motion. Further detailed research is necessary to investigate about environmental, biomechanical and individual factors to provide safe and health work practice among physiotherapists.